Opening the Sealed Book: Interpretations of the Book of Isaiah in Late Antiquity. By Joseph Blenkinsopp - Sawyer, John F. A. (The journal of theological studies, 2008)
Opening the Sealed Book follows the author's three-volume Anchor Bible Commentary on Isaiah published between 2000 and 2003, and considers the earliest period in the book's reception history, sectarian interpretations in particular. In a brilliant first chapter Blenkinsopp discusses books and literacy in the ancient world, and the notion of ‘book’ as applied to Isaiah, especially the verses about a ‘sealed book’ (29:11–12) and ‘my secret’ (24:16), and their literary relationship with Daniel and the apocalyptic tradition. He then considers how Isaiah is represented as ‘Author, Prophet and Man of God’, both in the book of Isaiah itself and in Chronicles, Ben Sira, Josephus, and other ancient Jewish traditions, and examines his role in the origins of Jewish apocalyptic sectarianism.